Internal Model Control (IMC)-Based Active and Reactive Power Control of Brushless Double-Fed Induction Generator with Notch Filter. (18th July 2022) - Memon, Ahsanullah; Bin Mustafa, Mohd Wazir; Laghari, Zohaib Hussain; Jumani, Touqeer Ahmed; Anjum, Waqas; Ullah, Shafi; Aman, Muhammad Naveed
Abstract : The increase in demand for electricity and, in particular, green energy has put renewable energy systems at the focal point of energy policy worldwide. The higher reliability of brushless doubly fed induction generators (BDFIGs) makes them suitable for offshore and remote wind energy generation (WEG) applications. Besides, controlling the active and reactive powers in an electrical power system is critical for optimal voltage regulation, reduced power losses, and enhanced utilization of installed equipment. However, the existing literature on BDFIG's active and reactive power control highlights the poor dynamic response and high transients with harmonic generation during inductive load insertion. It is because the Ziegler technique was employed to select PI gains, and the instantaneous reactive power theory was used to mitigate harmonics. Considering that, this paper proposes a vector control (VC) method for BDFIGs in wind turbines, in which the proportional-integral (PI) gains for internal model control (IMC) are optimized to improve the dynamic response of the active and reactive power during inductive load insertion. The proposed method reduces the complexity, time consumption, and uncertainty in making the optimal choice. In addition, to reduce a double fundamental frequency component to the point-of-common-coupling (PCC) voltage, the excellent characteristics of the notch filter are utilized in the grid-side converter (GSC)-based vector control scheme. The simulation results in MATLAB/Simulink show that the proposed IMC-based vector control scheme with a notch filter provides satisfactory results with a minimum peak value compared to existing techniques.